Makna Simbol Benda dalam Upacara Pemakaman Menurut Dayak Bahau Umaaq Luhat dan Gereja Katolik - Vinsensius Lai; Wilfridus Samdirgawijaya; G. Simon Devung (Gaudium Vestrum - Jurnal Kateketik Pastoral, 2019)
The research aimed to find and describe the symbols in the funeral rituals of the Dayak Bahau Umaaq Luhat and the Catholic Church. Indentifying material symbols used in the Dayak Bahau Umaaq Luhat funeral rituals and those in the funeral rituals according to the Catholic Church. Then, comparing the meaning of symbols in the traditional ceremonies of the death of the Dayak Bahau Umaaq Luhat and the Catholic Church. The research method is comparative descriptive, comparing several different components to find similarities and differences in the meanings of the material symbols used in the rituals. The result of the research showed in general the varieties of the material symbols used in the Dayak Bahau Umaaq Luhat funeral rituals and the Catholic Church rituals. The meaning of the material symbols used in the funeral riruals according to the Dayak Bahau Umaaq Luhat lead to the safety of the soul of the deceased and the safety of those who are still alive. While the meaning of the material symbols used in the Catholic Church funeral rituals leads more to the salvation of the soul of the person who dies.